Hong Kong Chinese aging adults voice financial care expectations in changing family and sociocultural contexts: implications for policy and services. Issue 5 (20th October 2019) - Bai, Xue
ABSTRACT: Despite being one of the world's wealthiest cities, approximately one-third of Hong Kong older adults live below the poverty line. Innovatively using the Photovoice research method, this study invited 36 Hong Kong Chinese aging adults to photograph images and voice their concerns and expectations regarding financial care. Insufficient government support, diminishing family support, insecurity and fear regarding future finances, and strong desire for self-sufficiency through early preparation and bridge employment were recurring themes observed in the participants' photographs and narratives. The shifting of the participants' financial care expectations from informal to formal sources in changing family and sociocultural contexts indicated that older people are in urgent need of policy reform from a needs-based to rights-based approach to foster empowerment and fulfill older people's rights of financial security, dignity and participation. Improving the retirement protection system should go hand in hand with encouraging family support and caregiving and creating age-friendly working environment for older residents. The findings of this study may have crucial policy implications for Hong Kong and other aging societies, especially those that share similar filial piety values and have seemingly ungenerous welfare systems.